W-plug via electromigration in CMOS process - 赵文彬 陈海峰 肖志强 李蕾蕾 于宗光 (Journal of semiconductors, 2009)
We analyze the failure mechanism of W-plug via electromigration made in a 0.5-μm CMOS SPTM process. Failure occurs at the top or bottom of a W-plug via. We design a series of via chains, whose size ranges from 0.35 to 0.55μm. The structure for the via electromigration test is a long via chain, and the layer in the via is Ti/TiN/W/TiN. Using a self-heated resistor to raise the temperature of the via chain allows the structure to be stressed at lower current densities, which does not cause significant joule heating in the plugs. This reduces the interaction between the plug and the plug contact resistance and the time-to-failure for the via chain. The lifetime of a W-plug via electromigration is on the order of 3×10^7S, i.e., far below the lifetime of metal electromigration. The study on W-plug via electromigraion in this paper is beneficial for wafer level reliability monitoring of the ultra-deep submicron CMOS multilayer metal interconnect process.